Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
DOI: 10.54337/aau424058297
|View full text |Cite
|
Sign up to set email alerts
|

Expressional prerequisites for targeted drug delivery to the pathological brain

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research. -You may not further distribute the material or use it for any profit-making activity or commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 301 publications
(456 reference statements)
0
1
0
Order By: Relevance
“…We found that VPA treatment increases the expression of Tfrc significantly after 6 hours in vitro, reaching an expression of three times greater than the controls and that the expression was back to baseline after 24 hours of treatment. To examine whether this effect was species-specific, we have conducted similar experiments in the rat where Tfrc increased 2.5-fold following VPA treatment [38].…”
Section: Discussionmentioning
confidence: 99%
“…We found that VPA treatment increases the expression of Tfrc significantly after 6 hours in vitro, reaching an expression of three times greater than the controls and that the expression was back to baseline after 24 hours of treatment. To examine whether this effect was species-specific, we have conducted similar experiments in the rat where Tfrc increased 2.5-fold following VPA treatment [38].…”
Section: Discussionmentioning
confidence: 99%